2015
DOI: 10.1111/cns.12420
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin Differentially Affects Neuronal Cholesterol and Amyloid‐β Production in vivo and in vitro

Abstract: Lovastatin modifies the mevalonate pathway without affecting cholesterol levels in vivo and is able to reduce Aβ levels only in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…These differences in the expression levels of HMGCR were analyzed by flow cytometry in infected cells treated with vehicle, MET or lovastatin. The results indicate that MET decreases HMGCR expression (Fig 4E) which is consistent with the results obtained by Madsen et al, 2015 whose demonstrated that MET decreases HMGCR expression and other genes related with lipid metabolism by transcriptional suppression of the steroid receptor coactivator 2 (SRC-2)[43] In contrast, lovastatin induced an increase in the amount of HMGCR (Fig 4E) confirming previous reports in hepatic and neuron cell lines [44]. This effect can be explained by the regulatory feedback induced by the reduction of intracellular cholesterol levels, which trigger HMGCR transcription [45].…”
Section: Resultssupporting
confidence: 91%
“…These differences in the expression levels of HMGCR were analyzed by flow cytometry in infected cells treated with vehicle, MET or lovastatin. The results indicate that MET decreases HMGCR expression (Fig 4E) which is consistent with the results obtained by Madsen et al, 2015 whose demonstrated that MET decreases HMGCR expression and other genes related with lipid metabolism by transcriptional suppression of the steroid receptor coactivator 2 (SRC-2)[43] In contrast, lovastatin induced an increase in the amount of HMGCR (Fig 4E) confirming previous reports in hepatic and neuron cell lines [44]. This effect can be explained by the regulatory feedback induced by the reduction of intracellular cholesterol levels, which trigger HMGCR transcription [45].…”
Section: Resultssupporting
confidence: 91%
“… Husain et al (2017) showed that rosuvastatin inhibited Aβ aggregation and ameliorated cognitive impairment in an in vivo study. Additionally, although lovastatin was able to diminish Aβ levels in vitro , it was unable to produce any effect on Aβ levels in the brains of the mice, even though the mevalonate pathway was significantly modified ( Mendoza-Oliva et al, 2015 ). Conversely, Tg2576 mice that were treated with lovastatin (the most brain permeable statin) showed an increase in Aβ production and senile plaque deposition ( Park et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol metabolism disorders in brain have been involved in neurodegenerative diseases such as AD . Scientific evidence has shown that the homeostasis of cholesterol in the brain is closely related to the metabolism of β‐amyloid peptides (Aβ), while the role of dietary cholesterol within the pathogenetic cascade of excessive Aβ deposition in the brain of AD needs to be further identified.…”
Section: Introductionmentioning
confidence: 99%